2016
DOI: 10.1063/1.4942213
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid transparent conductive electrodes with copper nanowires embedded in a zinc oxide matrix and protected by reduced graphene oxide platelets

Abstract: Transparent conductive electrodes (TCE) were fabricated by combining three emerging nanomaterials: copper nanowires (CuNWs), zinc oxide (ZnO) nano-particulate thin films, and reduced graphene oxide (rGO) platelets. Whereas CuNWs are responsible for essentially all of the electrical conductivity of our thin-film TCEs, the ZnO matrix embeds and strengthens the CuNW network in its adhesion to the substrate, while the rGO platelets provide a protective overcoat for the composite electrode, thereby improving its st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…A subsequent sheet resistance measurement confirms that the right-half of the sample is indeed devoid of CuNWs. In our previous work, it was demonstrated that, when an aluminum-doped zinc oxide (AZO) thin film is deposited on the CuNW film and then properly treated, adhesion to the substrate is significantly improved [24] . When meso-porous TiO2 is deposited directly on a bare CuNW film, using either spin-coating or doctor blade coating, the CuNWs are ripped off from the substrate, rendering the TCE non-conductive.…”
Section: Resultsmentioning
confidence: 99%
“…A subsequent sheet resistance measurement confirms that the right-half of the sample is indeed devoid of CuNWs. In our previous work, it was demonstrated that, when an aluminum-doped zinc oxide (AZO) thin film is deposited on the CuNW film and then properly treated, adhesion to the substrate is significantly improved [24] . When meso-porous TiO2 is deposited directly on a bare CuNW film, using either spin-coating or doctor blade coating, the CuNWs are ripped off from the substrate, rendering the TCE non-conductive.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the decreased transmittance by electroplating could be recovered by the formation of transparent oxide shell. Through a facile sol‐gel technique, Falco and co‐workers deposited AZO thin film onto the CuNW networks. After annealing in a forming environment (95% N 2 + 5% H 2 ), the as‐prepared hybrid TCE was resistant to scotch‐tape peel, and had excellent chemical and/or mechanical stability.…”
Section: Oxidation Mechanism and Antioxidation Strategiesmentioning
confidence: 99%